Intercultural Performance: Bharatanatyam in the practice of a Western choreographer - Touliatou, Lydia (Taideyliopiston Teatterikorkeakoulu, 2023)
This thesis examines the practice of a Greek choreographer trained in Bharatanatyam and in western dance techniques such as, ballet, Cunningham, Graham and release, through the lens of intercultural performance making. It touches on the challenges found in a culturally mixed practice and discusses cultural appropriation and persisting Orientalist notions in the discussion of classical Indian dance forms in the West. In the first chapter, I introduce my background in dance and how I have experienced the symbiosis of the eastern and western dance trainings. The chapter is divided chronologically, starting with my years as a student of Bharatanatyam in Greece and continuing with my formal dance training at Trinity Laban Conservatoire of Music and Dance in London. In the second chapter my latest choreographic work ‘Fera Matter’, is brought as the case example which initiates the conversation. I elaborate on the conception of the piece and the starting points which were drawn by Greek mythology. The making process is also examined in its interculturality and reveals discussions of the working group around cultural appropriation. Additionally, I touch on the overall dramaturgy of the piece, and I focus on the discoveries made through the employment of abhinaya as a choreographic tool. In the third chapter I view more microscopically the topics of intercultural performance making, cultural appropriation and Orientalist notions found in interculturalism, with an emphasis on how they appear in my own work and practice. The direction of my analysis is inspired by anthropologist Pallabi Chakravorty and dance writer Janet O’Shea. The fourth and final chapter consists of a comparative analysis of the praxis of Akram Khan and Shantala Shivalingappa, to highlight existing methods of employing classical Indian dance on western stages and to reveal nuances among different practices. The chapter concludes with a further exploration of the term ‘guru-less’ which appeared during my written exploration.
Keywords: Bharata Natyam; Bharatanatyam; Intercultural performance; transnationalism; Greek choreographer; classical Indian dance; tanssi; kulttuurienvälisyys; koreografit; koreografia; performanssi; taiteellinen työ; esittävät taiteet; esitykset; monikulttuurisuus; fi=koreografia|sv=koreografi|en=Choreography|